2017
DOI: 10.1080/20550340.2017.1330453
|View full text |Cite
|
Sign up to set email alerts
|

A world without Down’s syndrome? Online resistance on Twitter: #worldwithoutdowns and #justaboutcoping

Abstract: Presented by actress and comedian Sally Phillips, A World Without Down's Syndrome has brought important ethical debates regarding prenatal screening into the public domain. By talking to people with Down's syndrome, family members, and professionals, Sally has presented a nuanced and thorough examination of the type of world we are living in. Following the documentary, Twitter users have continued to engage with debates and have created a resilient platform for challenging public attitudes. This paper explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…A large proportion of posts in our Australian data-set reflected these ableist, systemburden viewpoints (often disintegrating into personal attacks). These responses also resonated with the meta-narratives of economic austerity and entitlement to support services found on Twitter in the UK, where Burch (2017) found that people with disability utilising services were positioned as 'parasites' and as 'a drain' on so-called 'hard-working taxpayers'. Although Australia is not in an explicit economic austerity landscape, within our data-set, 'economic burden' attitudes were continually raised in relation to resource parameters of the NDIS, the very system that is designed to improve inclusion and provide support for people with disability in Australia.…”
Section: The Presumption/construction Of People With Down Syndrome As An Economic Burden On Society and Drain On Public Resourcesmentioning
confidence: 80%
See 3 more Smart Citations
“…A large proportion of posts in our Australian data-set reflected these ableist, systemburden viewpoints (often disintegrating into personal attacks). These responses also resonated with the meta-narratives of economic austerity and entitlement to support services found on Twitter in the UK, where Burch (2017) found that people with disability utilising services were positioned as 'parasites' and as 'a drain' on so-called 'hard-working taxpayers'. Although Australia is not in an explicit economic austerity landscape, within our data-set, 'economic burden' attitudes were continually raised in relation to resource parameters of the NDIS, the very system that is designed to improve inclusion and provide support for people with disability in Australia.…”
Section: The Presumption/construction Of People With Down Syndrome As An Economic Burden On Society and Drain On Public Resourcesmentioning
confidence: 80%
“…A recent concern of the disability community has been the rise of online disability hate speech on social media platforms such as Twitter and Reddit, associated with broader ableism in society (Burch, 2017(Burch, , 2018. This online communication suggests a social slippage, challenging the steady progress towards community inclusion and empowerment for people with disabilities, as supported by the NDIS and other social policy initiatives.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Online activism and social media networks are calling for critical examinations of how people construct meanings around disability and mental health (Burch, 2017). Counternarratives that challenge public attitudes about disability and disablism have garnered media attention and given disabled persons a voice in debates that they would normally be excluded from (Theodorou & Mavrou, 2017).…”
Section: Psychiatric Resistance and Activismmentioning
confidence: 99%